Research Progress of the Prevention and Treatment of Metabolic Diseases Based on Short Chain Fatty Acids - ZENG Lin, ZHANG Pengxiang, HUANG Qian, WANG Gaoxiang, LI Huilin (Zhongguo quanke yixue, 2022)
Short chain fatty acids (SCFAs) are a class of saturated fatty acids containing 1-6 carbon atoms, which are mainly produced by specific flora in the intestine through the fermentation of dietary fiber, and play an important role in maintaining the homeostasis of the intestinal environment. Recent studies have shown that SCFAs can regulate glucose and lipid metabolism, regulate energy balance, maintain the intestinal barrier and reduce inflammatory responses, eventually participating in the occurrence and development of metabolic diseases such as type 2 diabetes mellitus, obesity, lipid metabolic disorders and nonalcoholic fat liver disease through the above multiple pathways. This article summarizes the mechanism of SCFAs regulating metabolism and the research progress in the prevention and treatment of metabolic diseases, in order to provide more reference materials for the prevention and treatment of metabolic diseases.